2022
DOI: 10.1101/2022.07.11.499639
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mismatch resolution for repeat-mediated deletions show a polarity that is mediated by MLH1

Abstract: Repeat-mediated deletions (RMDs) are a type of chromosomal rearrangement between two homologous sequences that causes loss of the sequence between the repeats, along with one of the repeats. Sequence divergence between repeats suppresses RMDs; the mechanisms of such suppression and of resolution of the mismatched bases remains poorly understood. We identified RMD regulators using a set of reporter assays in mouse cells that test two key parameters: repeat sequence divergence and the distances between one repea… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…In a model with a single mismatch in a 152-bp segment, SSA events exhibited a modest 60-80% bias in correcting the mismatch prompted by the shorter of the two nonhomologous tails (33 nt vs. 11 nt) and that the pattern is reversed when cleavage creates tails of 0 and 42 nt [36]. Another recent study by Trost et al [37] found that mismatches proximal to a nonhomologous tail were preferentially removed. However, unlike in budding yeast, Mlh1 as well as Msh6 caused a reduction in SSA outcomes with mismatched substrates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a model with a single mismatch in a 152-bp segment, SSA events exhibited a modest 60-80% bias in correcting the mismatch prompted by the shorter of the two nonhomologous tails (33 nt vs. 11 nt) and that the pattern is reversed when cleavage creates tails of 0 and 42 nt [36]. Another recent study by Trost et al [37] found that mismatches proximal to a nonhomologous tail were preferentially removed. However, unlike in budding yeast, Mlh1 as well as Msh6 caused a reduction in SSA outcomes with mismatched substrates.…”
Section: Discussionmentioning
confidence: 99%
“…Another recent study by Trost et al [37] found that mismatches proximal to a nonhomologous tail were preferentially removed. However, unlike in budding yeast, Mlh1 as well as Msh6 caused a reduction in SSA outcomes with mismatched substrates.…”
Section: ' Flap Structure Dictates the Bias Of Mismatch Repairmentioning
confidence: 96%